Adhesive composition, adhesive film, and antistatic surface protection film
Patent Information
- Application Number
- JP2023127160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2036-06-16
AI Technical Summary
【0022】 本発明によれば、優れた粘着性能及び帯電防止性能を有し、さらには低汚染性にも優れた粘着剤層が得られる粘着剤組成物、及びそれを用いた帯電防止表面保護フィルムを提供することができる。
Smart Images

Figure 0007629489000001 
Figure 0007629489000002 
Figure 0007629489000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition containing an antistatic agent, and an antistatic surface protective film. More specifically, the present invention relates to a pressure-sensitive adhesive composition containing a borate anion compound having a pentafluorophenyl group (C6F5 group) as an antistatic agent, and to a pressure-sensitive adhesive composition that has excellent adhesion and antistatic properties and can provide a pressure-sensitive adhesive layer that is also excellent in low contamination, and an antistatic surface protective film using the same. The present invention also provides a pressure-sensitive adhesive composition that can provide a pressure-sensitive adhesive layer that has excellent adhesion and antistatic properties and is also excellent in low contamination, for a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound and laminated on the surface of an optical film, and an antistatic surface protective film using the same. [Background technology]
[0002] When optical films such as polarizing plates, retardation plates, lens films for displays, anti-reflection films, hard coat films, transparent conductive films for touch panels, and other optical products such as displays using the same are manufactured and transported, a surface protective film is attached to the surface of the optical film to prevent the surface from being soiled or scratched in later processes. In order to improve work efficiency by eliminating the need to peel off the surface protective film and then reattach it, the appearance inspection of the optical film, which is an optical product, is sometimes performed with the surface protective film attached to the optical film.
[0003] Conventionally, a surface protection film having a pressure-sensitive adhesive layer on one side of a base film has been generally used in the manufacturing process of optical products to prevent scratches and adhesion of dirt. The surface protection film is attached to the optical film via a pressure-sensitive adhesive layer having a weak adhesive strength. The reason why the pressure-sensitive adhesive layer has a weak adhesive strength is that when a used surface protection film is peeled off and removed from the surface of the optical film, it can be easily peeled off, and the pressure-sensitive adhesive is prevented from adhering to and remaining on the optical film of the product, which is the adherend (preventing the occurrence of so-called adhesive residue).
[0004] In recent years, during the production process of display panels, there have been rare cases where the peeling charge voltage that is generated when peeling off and removing the surface protection film that has been attached to the optical film has destroyed circuit components such as driver ICs that control the display screen of the display panel, or damaged the alignment of liquid crystal molecules. In addition, the driving voltage is becoming lower in order to reduce the power consumption of display panels, and the breakdown voltage of driver ICs is also becoming lower accordingly. For this reason, in order to prevent problems caused by high peeling electrification voltage when peeling a surface protection film from an optical film that is an adherend, a surface protection film using an adhesive layer containing an antistatic agent to keep the peeling electrification voltage low has been proposed.
[0005] Furthermore, in recent years, in order to prevent the adhesion of dirt, fingerprints, and the like, a layer containing a fluorine compound has come to be provided on the surface of display panels and touch panels. For example, Patent Documents 1 and 2 describe an antireflection film and a polarizing plate in which a low refractive index layer provided on the outermost surface of the antireflection film contains hollow inorganic particles for imparting a low refractive index and a curable fluororesin for imparting antifouling properties. Furthermore, Patent Document 3 describes an antireflection film having a low refractive index layer made of perfluoroalkyl(meth)acrylate, modified polydimethylsiloxane having an acrylic group, a fluorine-containing compound having a polymerizable double bond, and hollow silica particles.
[0006] Patent Document 4 describes a surface protection film that is attached to an adherend having a functional layer formed by treatment with a fluorine-containing compound or a silicon-containing compound, and that has an acrylic pressure-sensitive adhesive layer to which is externally added a polyether-modified polyorganosiloxane, a fluorine-containing alkyl group-containing fluorine-containing surfactant, or an acrylic polymer containing fluorine or silicon, as a compound containing fluorine or silicon. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-277059 A [Patent Document 2] JP 2008-262187 A [Patent Document 3] JP 2015-55659 A [Patent Document 4] JP 2011-63712 A Summary of the Invention [Problem to be solved by the invention]
[0008] In an antistatic surface protective film having antistatic performance, it is essential to add an antistatic agent to the adhesive layer. Therefore, if the content of the antistatic agent contained in the adhesive layer is increased in order to improve the antistatic performance of the adhesive layer, when the antistatic surface protective film is attached to the adherend via the adhesive layer, the amount of the antistatic agent attached to the adherend increases, causing the adherend to be contaminated. Therefore, there is a trade-off between the antistatic performance and the low contamination property to the adherend. That is, it has been difficult to improve the low contamination property while maintaining the antistatic function. However, in recent years, the display panel has become higher in image quality and higher in quality, and the evaluation criteria for low contamination are becoming stricter, and an antistatic surface protective film that is excellent in low contamination property to the surface of the adherend even as a result of judgment by a strict evaluation method is required.
[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an adhesive composition which provides an adhesive layer having excellent adhesive performance and antistatic performance and further excellent low-fouling properties, and an antistatic surface protection film using the same. [Means for solving the problem]
[0010] The present inventors have come up with the technical idea of the present invention to limit the number of carbon atoms in the alkyl group of the alkyl (meth)acrylate constituting the main component of the acrylic polymer of the adhesive composition to a specific range, and to use a copolymer obtained by copolymerizing two or more alkyl (meth)acrylates in a specific combination in combination with an antistatic agent containing a borate anion having a pentafluorophenyl group. They have found that the adhesive composition based on this technical idea is an adhesive composition that has superior adhesive performance and antistatic performance compared to conventional adhesive compositions for surface protection films, and further provides an adhesive layer with excellent low-contamination properties, and have completed the present invention. In other words, the antistatic surface protection film formed using the pressure-sensitive adhesive composition of the present invention has excellent adhesive performance and antistatic performance against an adherend such as an anti-fouling layer containing a fluorine compound laminated on the surface of an optical film, or a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound, and further has excellent low contamination properties, thereby achieving both antistatic performance and low contamination properties.
[0011] That is, the present invention provides a pressure-sensitive adhesive composition containing an acrylic polymer, an antistatic agent, and a crosslinking agent, wherein the acrylic polymer is in a ratio of 1 to 50 parts by weight of (a1) at least one (meth)acrylic ester monomer having an alkyl group carbon number of C1 to C4 and 50 to 99 parts by weight of (a2) at least one (meth)acrylic ester monomer having an alkyl group carbon number of C5 to C18, relative to 100 parts by weight of (A) (meth)acrylic ester monomers having an alkyl group carbon number of C1 to C18, and the acrylic polymer contains at least one monomer selected from the group consisting of isooctyl (meth)acrylate, isononyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate in a ratio of 50 parts by weight or more among the (a2), and further contains a copolymer The present invention provides a pressure-sensitive adhesive composition, characterized in that the pressure-sensitive adhesive composition is an acrylic polymer that is a copolymer obtained by copolymerizing (B) at least one copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group and (C) at least one polyalkylene glycol mono(meth)acrylic acid ester monomer as a group of possible monomers, and the (D) antistatic agent is an ionic compound that comprises a borate anion having a pentafluorophenyl group (C6F5 group) and a cation and that is solid at a temperature of 25°C or higher and contains the ionic compound as an essential component in a ratio of 0.1 to 10 parts by weight per 100 parts by weight of the acrylic polymer, and the pressure-sensitive adhesive composition further contains (E) a crosslinking accelerator and (F) a keto-enol tautomer compound.
[0012] The cation of the ionic compound is preferably one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and ammonium.
[0013] The (B) copolymerizable monomer containing a hydroxyl group is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide, and the (B) copolymerizable monomer containing a carboxyl group is at least one selected from the group consisting of (meth)acrylic acid, carboxyl It is preferable that the compound is at least one selected from the group consisting of ethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid.
[0014] The (C) polyalkylene glycol mono(meth)acrylic acid ester monomer preferably contains at least one selected from polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate, in which the average repeat number of alkylene oxide constituting the polyalkylene glycol chain is 3 to 14 and the diester content in the monomer is 0.2% or less, in an amount of 1 to 50 parts by weight per 100 parts by weight of the acrylic polymer.
[0015] It is preferable that the (E) crosslinking accelerator is at least one selected from the group consisting of aluminum chelate compounds, titanium chelate compounds, and iron chelate compounds, and that the (E) crosslinking accelerator is contained in an amount of 0.001 to 0.5 parts by weight and the (F) keto-enol tautomer compound is contained in an amount of 0.1 to 300 parts by weight relative to 100 parts by weight of the acrylic polymer, and that the (F) / (E) weight part ratio is 70 to 1000.
[0016] The present invention also provides a pressure-sensitive adhesive film, characterized in that it comprises a pressure-sensitive adhesive layer formed by crosslinking the above pressure-sensitive adhesive composition laminated thereon.
[0017] The pressure-sensitive adhesive layer has a surface resistivity of 1.0×10 +12 It is preferable that the resistivity is Ω / □ or less, and the peeling electrification voltage for the low refractive index layer formed using the composition for forming a low refractive index layer containing a fluorine compound is ±0.3 kV or less.
[0018] The present invention also provides an antistatic surface protection film using the above-mentioned pressure-sensitive adhesive film.
[0019] The present invention also provides an antistatic surface protective film for polarizing plates, which uses the above-mentioned pressure-sensitive adhesive film.
[0020] The present invention also provides an optical film with a pressure-sensitive adhesive, comprising an optical film and a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition laminated on at least one surface of the optical film.
[0021] In the above pressure-sensitive adhesive film, it is preferable that one surface of the resin film opposite to the surface on which the pressure-sensitive adhesive layer is formed is subjected to an antistatic treatment and an antifouling treatment. Effect of the Invention
[0022] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition which can give a pressure-sensitive adhesive layer having excellent adhesion and antistatic properties and further excellent low-staining properties, and an antistatic surface protection film using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, the present invention will be described based on preferred embodiments.
[0024] The pressure-sensitive adhesive composition of the present invention is a pressure-sensitive adhesive composition containing an acrylic polymer, an antistatic agent, and a crosslinking agent, wherein the acrylic polymer contains 1 to 50 parts by weight of (a1) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C4 and 50 to 99 parts by weight of (a2) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C5 to C18, relative to 100 parts by weight in total of (A) (meth)acrylic acid ester monomers having an alkyl group carbon number of C1 to C18, and further contains 50 parts by weight or more of at least one selected from the group consisting of isooctyl (meth)acrylate, isononyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate among the (a2). The pressure-sensitive adhesive composition further comprises an acrylic polymer which is a copolymer obtained by copolymerizing (B) at least one copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group and (C) at least one polyalkylene glycol mono(meth)acrylic acid ester monomer, the copolymerizable monomer group being a group in which the (D) antistatic agent is an ionic compound which is composed of a borate anion having a pentafluorophenyl group (C6F5 group) and a cation and which is solid at a temperature of 25°C or higher and contains the ionic compound as an essential component in a ratio of 0.1 to 10 parts by weight per 100 parts by weight of the acrylic polymer, and the pressure-sensitive adhesive composition further comprises (E) a crosslinking accelerator and (F) a keto-enol tautomer compound.
[0025] Among (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18, (a1) at least one kind of (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4 includes butyl (meth)acrylate, isobutyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and isopropyl (meth)acrylate. In addition, (a2) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of 5 to 18 include pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, and ethylhexyl (meth)acrylate. Examples of such acrylates include silyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, myristyl (meth)acrylate, isomyristyl (meth)acrylate, cetyl (meth)acrylate, isocetyl (meth)acrylate, stearyl (meth)acrylate, and isostearyl (meth)acrylate.
[0026] In the acrylic polymer, the ratio of (a1) at least one kind of (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C4 to 100 parts by weight of the total of (A) (meth)acrylic acid ester monomers having an alkyl group carbon number of C1 to C18 is preferably 1 to 50 parts by weight, (a2) at least one kind of (meth)acrylic acid ester monomer having an alkyl group carbon number of C5 to C18 is preferably 50 to 99 parts by weight, (a1) at least one kind is more preferably 3 to 45 parts by weight, (a2) at least one kind is more preferably 5 to 45 parts by weight, (a2) at least one kind is more preferably 5 to 95 parts by weight, (a2) at least one kind is more preferably 8 to 40 parts by weight, (a2) at least one kind is most preferably 60 to 92 parts by weight.
[0027] In the acrylic polymer, the amount of at least one of (a2) selected from the group consisting of isooctyl (meth)acrylate, isononyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate is preferably 50 parts by weight or more, more preferably 50 to 99 parts by weight, even more preferably 55 to 97 parts by weight, particularly preferably 55 to 95 parts by weight, and most preferably 60 to 92 parts by weight, per 100 parts by weight of (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18.
[0028] (B) At least one of the copolymerizable vinyl monomers containing a hydroxyl group and / or a carboxyl group may be at least one of the copolymerizable vinyl monomers containing a hydroxyl group, or at least one of the copolymerizable vinyl monomers containing a carboxyl group. Alternatively, at least one of the copolymerizable vinyl monomers containing a hydroxyl group and at least one of the copolymerizable vinyl monomers containing a carboxyl group may be used in combination. Also, at least one of the copolymerizable vinyl monomers containing a hydroxyl group and a carboxyl group may be used.
[0029] Examples of the copolymerizable monomer containing a hydroxyl group (B) include hydroxyalkyl (meth)acrylates and hydroxyl group-containing (meth)acrylamides. Specific examples of these include at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. These copolymerizable monomers containing a hydroxyl group (B) do not have a polyalkylene glycol chain, unlike the polyalkylene glycol mono (meth)acrylic acid ester monomer (C) described later. The total of at least one kind of (B) copolymerizable monomer containing a hydroxyl group is preferably contained in an amount of 0.1 to 20 parts by weight, more preferably 0.5 to 15 parts by weight, particularly preferably 2.0 to 14.0 parts by weight, and most preferably 2.5 to 12.0 parts by weight, per 100 parts by weight of the acrylic polymer.
[0030] The (B) copolymerizable monomer containing a carboxyl group is preferably at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid. The total of at least one kind of (B) copolymerizable monomer containing a carboxyl group is preferably contained in an amount of 0.0 to 1.0 part by weight, more preferably 0.0 to 0.8 parts by weight, particularly preferably 0.0 to 0.5 parts by weight, and most preferably 0.0 to 0.3 parts by weight, per 100 parts by weight of the acrylic polymer. The acrylic polymer may not contain a copolymerizable monomer containing a carboxyl group as (B) the copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group (the ratio is 0.0 part by weight); however, when the acrylic polymer contains a copolymerizable monomer containing a carboxyl group, the ratio is preferably 0.01 to 1.0 part by weight, more preferably 0.05 to 0.8 parts by weight, particularly preferably 0.05 to 0.5 parts by weight, and most preferably 0.05 to 0.3 parts by weight, relative to 100 parts by weight of the acrylic polymer.
[0031] The polyalkylene glycol mono(meth)acrylic acid ester monomer (C) may be a compound in which one of the hydroxyl groups of a polyalkylene glycol is esterified as a (meth)acrylic acid ester. The (meth)acrylic acid ester group is a polymerizable group, so that it can be copolymerized with the acrylic polymer. The other hydroxyl group may remain as OH or may be an alkyl ether such as methyl ether or ethyl ether, or a saturated carboxylate such as acetate. The alkylene group of the polyalkylene glycol includes, but is not limited to, an ethylene group, a propylene group, a butylene group, etc. The polyalkylene glycol may be a copolymer of two or more polyalkylene glycols such as polyethylene glycol, polypropylene glycol, polybutylene glycol, etc. The copolymer of polyalkylene glycol includes polyethylene glycol-polypropylene glycol, polyethylene glycol-polybutylene glycol, polypropylene glycol-polybutylene glycol, etc., and the copolymer may be a block copolymer or a random copolymer. It is preferable that the average repeat number of alkylene oxide constituting the polyalkylene glycol chain of the polyalkylene glycol mono(meth)acrylate monomer (C) is 3 to 14. The "average repeat number of alkylene oxide" refers to the average number of repeats of alkylene oxide units in the "polyalkylene glycol chain" portion contained in the molecular structure of the polyalkylene glycol mono(meth)acrylate monomer (C). In the polyalkylene glycol mono(meth)acrylic acid ester monomer (C), the diester content in the monomer is preferably 0.2% or less. The "diester content in the monomer" refers to the content (wt%) of polyalkylene glycol di(meth)acrylic acid ester contained in the polyalkylene glycol mono(meth)acrylic acid ester monomer (C).
[0032] The (C) polyalkylene glycol mono(meth)acrylic acid ester monomer is preferably at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate. More specifically, polyethylene glycol-mono(meth)acrylate, polypropylene glycol-mono(meth)acrylate, polybutylene glycol-mono(meth)acrylate, polyethylene glycol-polypropylene glycol-mono(meth)acrylate, polyethylene glycol-polybutylene glycol-mono(meth)acrylate, polypropylene glycol-polybutylene glycol-mono(meth)acrylate, polyethylene glycol-polypropylene glycol-polybutylene glycol-mono(meth)acrylate; methoxypolyethylene glycol-(meth)acrylate, methoxypolypropylene glycol-(meth)acrylate, methoxypolybutylene glycol-(meth)acrylate, methoxy-polyethylene glycol-polypropylene glycol-(meth)acrylate, methoxy-polyethylene glycol methoxy-polybutylene glycol-polybutylene glycol-(meth)acrylate, methoxy-polyethylene glycol-polypropylene glycol-polybutylene glycol-(meth)acrylate; ethoxypolyethylene glycol-(meth)acrylate, ethoxypolypropylene glycol-(meth)acrylate, ethoxypolybutylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polypropylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polybutylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polybutylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polybutylene glycol-(meth)acrylate, ethoxy-polypropylene glycol-polybutylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polypropylene glycol-polybutylene glycol-(meth)acrylate, and the like. The at least one or more kinds of (C) polyalkylene glycol mono(meth)acrylic acid ester monomers are preferably contained in a total amount of 1 to 50 parts by weight, more preferably 1 to 40 parts by weight, particularly preferably 1 to 30 parts by weight, and most preferably 2 to 25 parts by weight, relative to 100 parts by weight of the acrylic polymer.
[0033] (D) The antistatic agent contains, as an essential component, an ionic compound that is composed of a borate anion having a pentafluorophenyl group (C6F5 group) and a cation, and that is solid at a temperature of 25°C or higher and has a melting point of 25°C or higher. The borate anion having a pentafluorophenyl group (C6F5 group) is, for example, (C6F5)4B - , (C6F5)3(C6H5)B - , (C6F5)2(C6H5)2B - , (C6F5)(C6H5)3B - , etc.
[0034] Examples of the cation of the ionic compound include nitrogen-containing onium cations such as pyridinium, imidazolium, pyrimidinium, pyrazolium, pyrrolidinium, and ammonium, onium cations such as phosphonium cations and sulfonium cations, carbocations such as methylium, and alkali metal cations such as lithium. Among them, one selected from the group of cations consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and ammonium is preferred. When these cations are organic cations, the organic cations can have one or more substituents. Examples of the substituent of the organic cation include aliphatic groups such as alkyl groups, and aromatic groups such as phenyl groups. As the (D) antistatic agent, it is preferable that the ionic compound is contained in an amount of 0.1 to 10 parts by weight per 100 parts by weight of the acrylic polymer.
[0035] (D) Specific examples of the ionic compound that can be used as the antistatic agent include triphenylmethylium tetrakis(pentafluorophenyl)borate salt, 1-nonylpyridinium tetrakis(pentafluorophenyl)borate salt, 1-octylpyridinium tetrakis(pentafluorophenyl)borate salt, 1-dodecylpyridinium tetrakis(pentafluorophenyl)borate salt, lithium tetrakis(pentafluorophenyl)borate salt, 2-methyl-1-dodecylpyridinium tetrakis(pentafluorophenyl)borate salt, and the like.
[0036] The (E) crosslinking accelerator may be any substance that functions as a catalyst for the reaction (crosslinking reaction) between the acrylic polymer and the crosslinking agent when a polyisocyanate compound is used as the crosslinking agent, and examples of such crosslinking accelerator include amine compounds such as tertiary amines, metal chelate compounds, organotin compounds, organolead compounds, organozinc compounds, and other organometallic compounds. In the present invention, the crosslinking accelerator is preferably a metal chelate compound or an organotin compound.
[0037] A metal chelate compound is a compound in which one or more polydentate ligands L are bonded to a central metal atom M. The metal chelate compound may or may not have one or more monodentate ligands X bonded to the metal atom M. For example, the general formula of a metal chelate compound having one metal atom M is M(L) m (X) n When m is 2 or more, m L's may be the same ligand or different ligands. When n is 2 or more, n X's may be the same ligand or different ligands.
[0038] Examples of the metal atom M include Fe, Ni, Mn, Cr, V, Ti, Ru, Zn, Al, Zr, and Sn. Examples of the polydentate ligand L include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone (also known as 2,4-pentanedione), 2,4-hexanedione, and benzoylacetone. These are keto-enol tautomer compounds, and in the polydentate ligand L, the enol may be deprotonated to form an enolate (e.g., acetylacetonate). Examples of the monodentate ligand X include halogen atoms such as chlorine and bromine atoms, acyloxy groups such as pentanoyl, hexanoyl, 2-ethylhexanoyl, octanoyl, nonanoyl, decanoyl, dodecanoyl, and octadecanoyl groups, and alkoxy groups such as methoxy, ethoxy, n-propoxy, isopropoxy, and butoxy groups.
[0039] Specific examples of metal chelate compounds include iron tris(2,4-pentanedionato)(III), iron trisacetylacetonate, titanium trisacetylacetonate, ruthenium trisacetylacetonate, zinc bisacetylacetonate, aluminum trisacetylacetonate, zirconium tetrakisacetylacetonate, iron tris(2,4-hexanedionato)(III), zinc bis(2,4-hexanedionato), titanium tris(2,4-hexanedionato), aluminum tris(2,4-hexanedionato), and zirconium tetrakis(2,4-hexanedionato).
[0040] Examples of organotin compounds include dialkyltin oxide, fatty acid salts of dialkyltin, and fatty acid salts of stannous tin. Traditionally, dibutyltin compounds have been widely used, but in recent years, the toxicity of organotin compounds has been pointed out, and tributyltin (TBT) contained in dibutyltin compounds in particular is also a concern as an endocrine disrupting substance. From the viewpoint of safety, long-chain alkyltin compounds such as dioctyltin compounds are preferred. Specific examples of organotin compounds include dioctyltin oxide and dioctyltin dilaurate. Although Sn compounds can be used provisionally, in the future, in view of the trend toward the use of safer substances, it is preferable to use metal chelate compounds such as Al, Ti, and Fe, which are safer than Sn. The crosslinking accelerator (E) in the pressure-sensitive adhesive composition according to the present invention is preferably at least one selected from the group consisting of aluminum chelate compounds, titanium chelate compounds, and iron chelate compounds. The crosslinking accelerator (E) is preferably contained in an amount of 0.001 to 0.5 parts by weight based on 100 parts by weight of the acrylic polymer.
[0041] Examples of the (F) keto-enol tautomer compound include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. These compounds block the isocyanate groups of the crosslinking agent in a pressure-sensitive adhesive composition using a polyisocyanate compound as a crosslinking agent, thereby suppressing excessive viscosity increase and gelation of the pressure-sensitive adhesive composition after blending with the crosslinking agent, and thereby extending the pot life of the pressure-sensitive adhesive composition. The (F) keto-enol tautomer compound is preferably contained in a proportion of 0.1 to 300 parts by weight based on 100 parts by weight of the acrylic polymer.
[0042] Since the (F) keto-enol tautomer compound has an effect of suppressing crosslinking, in contrast to the (E) crosslinking accelerator, it is preferable to appropriately set the ratio of the (F) keto-enol tautomer compound to the (E) crosslinking accelerator. In order to extend the pot life of the pressure-sensitive adhesive composition and improve its storage stability, the (F) / (E) weight part ratio is preferably 70 to 1000, more preferably 70 to 700, and particularly preferably 80 to 600.
[0043] In the pressure-sensitive adhesive composition of the present invention, the pressure-sensitive adhesive polymer is crosslinked when the pressure-sensitive adhesive layer is formed. As a method for causing the crosslinking reaction, crosslinking may be performed by photocrosslinking using ultraviolet light (UV) or the like, but it is preferable that the pressure-sensitive adhesive composition contains a crosslinking agent. Examples of the crosslinking agent include bifunctional or trifunctional or higher isocyanate compounds, bifunctional or trifunctional or higher epoxy compounds, bifunctional or trifunctional or higher acrylate compounds, metal chelate compounds, etc. Among these, polyisocyanate compounds (bifunctional or trifunctional or higher isocyanate compounds) are preferred. The crosslinking agent is preferably contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the acrylic polymer.
[0044] The bifunctional or higher isocyanate compound may be at least one or more selected from polyisocyanate compounds having at least two isocyanate (NCO) groups in one molecule. Polyisocyanate compounds are classified into aliphatic isocyanates, aromatic isocyanates, acyclic isocyanates, alicyclic isocyanates, and the like, and any of them may be used. Specific examples of polyisocyanate compounds include aliphatic isocyanate compounds such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and trimethylhexamethylene diisocyanate (TMDI), and aromatic isocyanate compounds such as diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), hydrogenated xylylene diisocyanate (H6XDI), dimethyldiphenylene diisocyanate (TOID), and tolylene diisocyanate (TDI).
[0045] Examples of trifunctional or higher isocyanate compounds include biuret modified or isocyanurate modified difunctional isocyanate compounds (compounds having two NCO groups in one molecule), and adducts (polyol modified compounds) with trivalent or higher polyols (compounds having at least three OH groups in one molecule) such as trimethylolpropane (TMP) or glycerin. As the difunctional or higher functional isocyanate compound, it is possible to use only a trifunctional isocyanate compound or only a bifunctional isocyanate compound. It is also possible to use a trifunctional isocyanate compound and a bifunctional isocyanate compound in combination.
[0046] The bifunctional isocyanate compound may be an acyclic aliphatic isocyanate compound produced by reacting a diisocyanate compound with a diol compound. For example, when a diisocyanate compound is represented by the general formula "O=C=NXN=C=O" (where X is a divalent group) and a diol compound is represented by the general formula "HO-Y-OH" (where Y is a divalent group), an example of a compound produced by reacting a diisocyanate compound with a diol compound is a compound represented by the following general formula Z.
[0047] [General formula Z] O=C=NX-(NH-CO-OYO-CO-NH-X) n -N=C=O
[0048] Here, n is an integer of 0 or more. When n is 0, the general formula Z represents "O=C=NXN=C=O". The bifunctional acyclic aliphatic isocyanate compound may contain a compound in which n is 0 in the general formula Z (a diisocyanate compound unreacted with a diol compound), but it is preferable to contain a compound in which n is an integer of 1 or more as an essential component. The bifunctional acyclic aliphatic isocyanate compound may be a mixture of multiple compounds in which n in the general formula Z is different.
[0049] The diisocyanate compound represented by the general formula "O=C=NXN=C=O" is an aliphatic diisocyanate. X is preferably an acyclic aliphatic divalent group. The aliphatic diisocyanate is preferably one or more selected from the group consisting of tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate.
[0050] The diol compound represented by the general formula "HO-Y-OH" is an aliphatic diol. Y is preferably an acyclic aliphatic divalent group. The diol compound is preferably one or more selected from the group consisting of 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol monohydroxypivalate, polyethylene glycol, and polypropylene glycol.
[0051] Furthermore, as other components, the pressure-sensitive adhesive composition of the present invention can appropriately contain known additives such as surfactants, curing accelerators, plasticizers, fillers, curing retarders, processing aids, antioxidants, antioxidants, polyether-modified siloxane compounds, etc. These can be used alone or in combination of two or more kinds.
[0052] The acrylic polymer used in the pressure-sensitive adhesive composition of the present invention can be synthesized by copolymerizing (a1) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C4 as (A) (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18, and (a2) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C5 to C18 as (A) and (B) at least one copolymerizable vinyl monomer having a hydroxyl group and / or a carboxyl group, and (C) at least one polyalkylene glycol mono(meth)acrylic acid ester monomer as (C) copolymerizable monomer group. The polymerization method of the acrylic polymer is not particularly limited, and any appropriate polymerization method such as solution polymerization or emulsion polymerization can be used.
[0053] In producing the acrylic polymer, it is preferable to carry out the polymerization reaction under anhydrous conditions, such as solution polymerization using an anhydrous organic solvent, in order to reduce the inclusion of moisture in the pressure-sensitive adhesive composition. In particular, it is preferable to use the polyalkylene glycol mono(meth)acrylic acid ester monomer (C) having a low moisture content, since it is highly hydrophilic. In order to avoid an increase in the viscosity of the pressure-sensitive adhesive composition, it is preferable to minimize the amount of polyfunctional (bifunctional or higher) monomers that can function as crosslinking agents among the monomers used in the production of the acrylic polymer. In particular, it is preferable to use polyalkylene glycol mono(meth)acrylic acid ester monomer (C) with a small diester content, since the corresponding diester content is a di(meth)acrylic acid ester of a bifunctional monomer.
[0054] The pressure-sensitive adhesive composition of the present invention can be prepared by blending the acrylic polymer with a crosslinking agent, an antistatic agent, a crosslinking accelerator, and a keto-enol tautomer compound, and further with any additives as appropriate.
[0055] The adhesive layer obtained by crosslinking the adhesive composition preferably has an adhesive strength of 0.05 to 0.1 N / 25 mm at a low peeling speed of 0.3 m / min, and an adhesive strength of 1.0 N / 25 mm or less at a high peeling speed of 30 m / min. This provides performance with little change in adhesive strength depending on the peeling speed, and enables rapid peeling even at high-speed peeling. In addition, when the antistatic surface protective film is peeled off once for re-adhesion, it does not require excessive force and is easy to peel off from the adherend.
[0056] The gel fraction of the pressure-sensitive adhesive layer (crosslinked pressure-sensitive adhesive) obtained by crosslinking the pressure-sensitive adhesive composition of the present invention is preferably 95 to 100%. With such a high gel fraction, the adhesive strength is not excessively high at a low peel speed, and the elution of unpolymerized monomers or oligomers from the acrylic polymer is reduced, resulting in improved low-staining properties and durability at high temperatures and high humidity, and thus suppressing staining of the adherend.
[0057] The pressure-sensitive adhesive composition of the present invention has a good balance of the above-mentioned components (A) to (F), and therefore has excellent antistatic performance, a good balance of adhesive strength at low and high peel speeds, and also has excellent low-staining properties. Therefore, it can be suitably used as an antistatic surface protection film for optical films such as polarizing plates, optical films with pressure-sensitive adhesives, etc., and therefore has high industrial utility value.
[0058] The pressure-sensitive adhesive film of the present invention is formed by laminating a pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition of the present invention on at least one side of a resin film. The antistatic surface protective film of the present invention is formed by using the pressure-sensitive adhesive film of the present invention, and can be suitably used as an antistatic surface protective film for optical films such as polarizing plates and optical members. The pressure-sensitive adhesive-attached optical film of the present invention is formed by laminating a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition of the present invention on at least one side of an optical film.
[0059] Examples of the polarizing plate that is the adherend of the pressure-sensitive adhesive layer include a polarizing plate that has been subjected to a low-reflection surface treatment to reduce the reflectance to 2% or less (LR polarizing plate) and a polarizing plate that has been subjected to a low-reflection surface treatment to reduce the reflectance to 2% or less and an anti-glare treatment (AG-LR polarizing plate). In addition, optical films and optical members such as polarizing plates can have a surface layer, such as a low-refractive index layer formed using a composition for forming a low-refractive index layer containing a fluorine compound, or an anti-fouling layer containing a fluorine compound, on the outermost surface to which the pressure-sensitive adhesive layer is attached. An example of a composition for forming a low refractive index layer (surface layer) containing a fluorine compound is a fluororesin composition. In order to reduce the refractive index of the low refractive index layer, the composition for forming the low refractive index layer may contain hollow particles such as hollow silica particles. The refractive index of the low refractive index layer may be, for example, 1.2 to 1.4. The low reflection surface treatment may have a high refractive index layer having a higher refractive index than the low refractive index layer on the surface, below the low refractive index layer. The refractive index of the high refractive index layer may be, for example, 1.5 to 1.9. A medium refractive index layer having a refractive index between the low refractive index layer and the high refractive index layer may be laminated.
[0060] The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has a surface resistivity of 1.0×10 +12 It is preferable that the surface resistivity is Ω / □ or less. In addition, after the adhesive layer is attached to a low refractive index layer (anti-fouling layer) formed using a composition for forming a low refractive index layer containing a fluorine compound, the peeling electrification voltage when the adhesive layer is peeled off is "±0.3 kV or less". In the present invention, "±0.3 kV or less" means 0 to -0.3 kV and 0 to +0.3 kV, that is, -0.3 to +0.3 kV. If the surface resistivity is large, the performance of dissipating static electricity generated by charging when the adhesive layer is peeled off from the adherend is poor. Therefore, by sufficiently reducing the surface resistivity, the peeling electrification voltage generated by static electricity generated when the adhesive layer is peeled off from the adherend is reduced, and it is possible to suppress the influence on the electric control circuit of the adherend.
[0061] The base film of the pressure-sensitive adhesive layer and the release film (separator) that protects the adhesive surface can be made of a resin film such as a polyester film. The release film is subjected to a release treatment with a silicone-based or fluorine-based release agent on the surface that is to be joined to the adhesive surface of the pressure-sensitive adhesive layer. The resin film serving as the base film may be subjected to antistatic treatment and antifouling treatment on the side opposite to the side on which the pressure-sensitive adhesive layer is formed. Examples of the antistatic treatment of the resin film include antistatic treatment by coating or kneading an antistatic agent. Examples of the antifouling treatment of the resin film include antifouling treatment by silicone-based or fluorine-based release agents or coating agents, silica fine particles, etc. EXAMPLES
[0062] The present invention will now be further described with reference to examples.
[0063] <Production of Pressure-Sensitive Adhesive Composition> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 15 parts by weight of methyl acrylate, 85 parts by weight of 2-ethylhexyl acrylate, 15.0 parts by weight of 8-hydroxyoctyl acrylate, 0.1 parts by weight of acrylic acid, 20 parts by weight of polypropylene glycol monoacrylate (n=12), and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile was dropped as a polymerization initiator over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer solution having a weight average molecular weight of 500,000 and used in Example 1. To this acrylic polymer solution, 9.0 parts by weight of acetylacetone was added and stirred, and then 2.0 parts by weight of Coronate HX (an isocyanurate of a hexamethylene diisocyanate compound), 0.1 parts by weight of titanium trisacetylacetonate, and 0.9 parts by weight of triphenylmethylium tetrakis(pentafluorophenyl)borate were added and mixed with stirring to obtain the adhesive composition of Example 1.
[0064] [Examples 2 to 6 and Comparative Examples 1 to 3] Pressure-sensitive adhesive compositions of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the formulations of the pressure-sensitive adhesive composition of Example 1 were as shown in Tables 1 and 2, respectively.
[0065] [Table 1]
[0066] [Table 2]
[0067] In Tables 1 and 2, the numerical values in parts by weight are shown in parentheses, with the total of the (a1) group and the (a2) group being 100 parts by weight. The compound names of the abbreviations of each component used in Tables 1 and 2 are shown in Tables 3 and 4. Coronate (registered trademark) HX, HL, and L are product names of Tosoh Corporation, and Takenate (registered trademark) D-140N, D-127N, and D-110N are product names of Mitsui Chemicals, Inc.
[0068] Regarding the polyalkylene glycol mono(meth)acrylic acid ester monomer (C) in Table 3, the numerical value of "n" is the average repeat number of the alkylene oxide constituting the polyalkylene glycol chain. In C-1 to C-5 used in Examples 1 to 6, the average repeat number of the alkylene oxide constituting the polyalkylene glycol chain is 3 to 14, and the diester content in the monomer is 0.2% or less. The diester content in the monomer of C-6 is 0.8%.
[0069] Regarding the (D) antistatic agent in Table 4, D-1 to D-5 used in Examples 1 to 6 are ionic compounds having a melting point of 25° C. or more and being solid at a temperature of 25° C. D-6 is an ionic compound having a melting point of 15° C. and being liquid at a temperature of 25° C.
[0070] [Table 3]
[0071] [Table 4]
[0072] <Synthesis of bifunctional isocyanate compounds> The bifunctional isocyanate compounds of Synthesis Examples 1 and 2 were synthesized by the following method. As shown in Tables 5 and 6, a diisocyanate and a diol compound were mixed in a molar ratio of NCO / OH=16 and reacted at 120°C for 3 hours, and then the unreacted diisocyanate was removed under reduced pressure using a thin-film evaporator to obtain the desired bifunctional isocyanate compound.
[0073] [Table 5]
[0074] [Table 6]
[0075] <Manufacture of antistatic surface protection film> [Example 1] The adhesive composition of Example 1 produced as described above was applied onto a release film made of a silicone resin-coated polyethylene terephthalate (PET) film, and then the solvent was removed by drying at 90° C. to obtain an adhesive sheet with an adhesive layer thickness of 25 μm. Thereafter, the adhesive sheet was transferred to the opposite side of the antistatic and antifouling treated side of a polyethylene terephthalate (PET) film that had been antistatic and antifouling treated on one side, to obtain an antistatic surface protection film of Example 1 having a laminated structure of "antistatic and antifouling treated PET film / adhesive layer / release film (silicone resin coated PET film)". [Examples 2 to 6 and Comparative Examples 1 to 3] The antistatic surface protective films of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as in the preparation of the antistatic surface protective film of Example 1 above.
[0076] <Test methods and evaluation> The antistatic surface protection films of Examples 1 to 6 and Comparative Examples 1 to 3 were aged for 7 days under an atmosphere of 23°C and 50% RH, and then the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, which was used as a sample for measuring surface resistivity. The antistatic surface protection film with the pressure-sensitive adhesive layer exposed was then attached to the surface of a polarizing plate via the pressure-sensitive adhesive layer, left for one day, autoclaved at 50°C and 5 atm for 20 minutes, and left for a further 12 hours at room temperature to prepare a sample for measuring adhesive strength, peeling electrification voltage, and low contamination. The polarizing plate to be adhered was an LR polarizing plate or an AG-LR polarizing plate, which had been subjected to a low reflection surface treatment and had a low refractive index layer formed on the surface using a composition for forming a low refractive index layer containing a fluorine compound.
[0077] <Adhesive strength> The measurement sample obtained above (a 25 mm wide antistatic surface protection film attached to the surface of the polarizing plate of the adherend) was peeled in a 180° direction at a low peel speed (0.3 m / min) and a high peel speed (30 m / min) using a tensile tester, and the measured peel strength was taken as the adhesive strength (N / 25 mm).
[0078] <Surface resistivity> After aging, and before bonding the adherend to a polarizing plate, the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, and the surface resistivity (Ω / □) of the adhesive layer was measured using a resistivity meter Hiresta UP-HT450 (manufactured by Mitsubishi Chemical Analytech).
[0079] <Peeling charge voltage> When the measurement sample obtained above was peeled off at an angle of 180° at a tensile speed of 30 m / min, the voltage (charged voltage) generated by the polarizing plate of the adherend being charged was measured using high-precision electrostatic sensors SK-035 and SK-200 (manufactured by Keyence Corporation), and the maximum measured value was taken as the peeling charged voltage (kV).
[0080] <Low contamination> The polarizing plate of the adherend was attached to one side of a glass plate via an adhesive layer such as a double-sided adhesive tape using a laminating machine. Then, the adhesive layer of an antistatic surface protective film was attached to the surface of the polarizing plate of the adherend using a laminating machine. After storing for 3 days and 30 days under an environment of 23°C and 50% RH, the antistatic surface protective film was peeled off, and the surface of the polarizing plate of the adherend was visually observed for contamination. The low contamination property was evaluated as follows: if there was no contamination on the surface of the polarizing plate of the adherend after either 3 days or 30 days of storage, it was evaluated as "○"; if there was slight contamination after either 3 days or 30 days of storage, it was evaluated as "△"; if there was contamination, it was evaluated as "×".
[0081] The evaluation results are shown in Table 7. The surface resistivity is expressed as "m×10 +n " is expressed as "mE+n" (where m is an arbitrary real number, and n is a positive integer). "Surface treatment of polarizing plate" indicates the type of polarizing plate of the adherend (LR treatment or AG-LR treatment).
[0082] [Table 7]
[0083] The antistatic surface protective films of Examples 1 to 6 have been subjected to LR treatment or AG-LR treatment and have a low refractive index layer containing a fluorine compound on the surface thereof. The adhesive strength of the adherend to a polarizing plate at a low peeling speed of 0.3 m / min is 0.05 to 0.1 N / 25 mm, and the adhesive strength of the adherend at a high peeling speed of 30 m / min is 1.0 N / 25 mm or less, and the surface resistivity is 1.0 × 10 +12 The peeling electrification voltage was less than ±0.3 kV, and the low contamination properties were also excellent when stored for 3 days and 30 days. In other words, the antistatic surface protective film of the present invention has excellent adhesion and antistatic properties to adherends, and also has excellent low contamination properties, thereby achieving a balance between antistatic properties and low contamination properties.
[0084] In addition, the antistatic surface protection film of Comparative Example 1, in which the acrylic polymer did not contain (a1) a (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4, and the (D) antistatic agent was an ionic compound having a melting point of 15°C and being liquid at a temperature of 25°C, had a high peeling electrification voltage and was somewhat inferior in anti-fouling properties. In addition, the antistatic surface protection film of Comparative Example 2, in which the acrylic polymer contained 80 parts by weight of (a1) (meth)acrylic ester monomers having an alkyl group with a carbon number of C1 to C4, and more than 20 parts by weight of (a2) (meth)acrylic ester monomers having an alkyl group with a carbon number of C5 to C18, per 100 parts by weight of (A) (meth)acrylic ester monomers having an alkyl group with a carbon number of C1 to C18, and (D) the antistatic agent was an ionic compound having a melting point of 15°C and being liquid at a temperature of 25°C, had excessively high adhesive strength, high surface resistivity, high peeling electrification voltage, and poor low contamination properties. In addition, the antistatic surface protection film of Comparative Example 3, in which the acrylic polymer did not contain the (C) polyalkylene glycol mono(meth)acrylic acid ester monomer and the pressure-sensitive adhesive composition did not contain the (D) antistatic agent, had high surface resistivity, high peeling electrification voltage, and poor anti-fouling properties. Thus, the antistatic surface protection films of Comparative Examples 1 to 3 were unable to achieve both excellent low-staining properties for adherends and excellent antistatic performance.
Claims
1. A pressure-sensitive adhesive composition comprising an acrylic polymer, (D) an antistatic agent, and a crosslinking agent, The acrylic polymer is (A) per 100 parts by weight of (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18, (a1) 1 to 50 parts by weight of at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4; (a2) 50 to 99 parts by weight of at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of 5 to 18; Further, as a copolymerizable monomer group, (B) at least one copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group; (C) at least one polyalkylene glycol mono(meth)acrylic acid ester monomer, (However, acrylic polymers having at least one of a nitrogen-containing vinyl monomer not containing a hydroxyl group or an alkoxy-containing alkyl (meth)acrylate monomer copolymerized therewith are excluded.) The (D) antistatic agent is a pentafluorophenyl group (C 6 F 5 a borate anion having a borate group and a cation, and has a melting point of 25° C. or higher and is solid at 25° C., the crosslinking agent is a bifunctional or trifunctional or higher functional isocyanate compound, the pressure-sensitive adhesive composition contains the crosslinking agent in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the acrylic polymer, the pressure-sensitive adhesive composition further comprises (E) a crosslinking accelerator and (F) a keto-enol tautomer compound, the (E) crosslinking accelerator being at least one selected from the group consisting of an aluminum chelate compound, a titanium chelate compound, and an iron chelate compound; A pressure-sensitive adhesive composition having a peeling electrification voltage of ±0.3 kV.
2. the hydroxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide, the copolymerizable monomer containing a carboxyl group is at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid; The pressure-sensitive adhesive composition according to claim 1, characterized in that the (C) polyalkylene glycol mono(meth)acrylic acid ester monomer is at least one selected from polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate, in which the average repeat number of alkylene oxides constituting the polyalkylene glycol chain is 3 to 14 and the diester content in the monomer is 0.2% or less.
3. 3. A pressure-sensitive adhesive film comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition according to claim 1 or 2 laminated on one side thereof.
4. An antistatic surface protective film, comprising the pressure-sensitive adhesive film according to claim 3.
5. An antistatic surface protective film for a polarizing plate, comprising the pressure-sensitive adhesive film according to claim 3 .
Citation Information
Patent Citations
Antireflection film, polarizing plate, and image display device
JP2008262187A
Antistat and application thereof
JP2010138234A
Antireflection film and polarizing plate including the same
JP2010277059A
Optical adhesive and optical adhesive sheet using the same
JP2011037927A
Surface protective film
JP2011063712A